Pelatihan dan Pendampingan Pembuatan Bahan Ajar Berbasis Etnomatematika dengan Augmented Reality Bagi Guru MTs di Kabupaten Lumajang - Mohammad Ridho'i; Fahmi Abdul Halim; Nimas Dian Fitria; Yasinta Dwi Adinda; Aros Ta’ala (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
This Community Partnership Program (PKM) aims to improve the competence of mathematics teachers at Madrasah Tsanawiyah (MTs) in Lumajang Regency in developing ethnomathematics-based teaching materials integrated with Augmented Reality (AR) technology. This program was initiated due to the minimal use of local culture in mathematics learning and the low ability of teachers to develop innovative teaching materials. The activity was carried out in four main stages: socialization, training, technology application, and mentoring and evaluation. The training included an introduction to the concept of ethnomathematics, the preparation of differentiated teaching materials, and the creation of AR-based learning media using Unity 3D, Blender, Geogebra, and Vuforia. The results of the activity showed an increase in teachers' understanding of the concept of ethnomathematics and their ability to integrate the local cultural values of Lumajang into mathematics learning. In addition, teachers successfully produced contextual AR-based interactive teaching materials in line with the spirit of the Merdeka Curriculum. This activity also strengthened collaboration between lecturers, students, and teachers of the MTs Wilker III Mathematics MGMP and became a model for continuous training in the development of innovative learning media based on local wisdom and digital technology.